Role of prostatic basal cell marker in diagnosis of prostatic lesions - SUBATHRA K, (International Journal of Pharma and Bio Sciences, 2017)
Prostatic biopsy interpretation and differentiating between premalignant and malignant lesions is a problem for practicing pathologist in many cases especially in TURP cases. An important diagnostic criterion in the differentiation is the loss of basal cell layer in adenocarcinoma and its presence in the benign lesions. This study aims at the evaluation of role of basal cell immunohisto chemical markers in different benign, premalignant and malignant lesions of prostate. From one hundred and eight transurethral resection of prostate specimens ten cases selected and immunohistochemical study with p63 was done. Continuous staining of basal cells was observed in benign glands, foci of low grade PIN and atypical adenoamatous hyperplasia. Focal discontinuity in basal cell staining was observed in high grade PIN areas. Complete absence of basal cell staining was seen in adenocarcinoma. Discontinuous basal cell staining was seen in disrupted glands of Granulomatous prostatitis. In this study malignant glands consistently failed to express immunoreactivity to antibody against p63, whereas normal prostatic acini invariably were stained for basal cells. Increasing grades of PIN were associated with progressive disruption of basal cell layer. In our study suspected areas of atypical adenomatous hyperplasia in benign prostatic hyperplasia showed continuous staining with p63 which proved that the lesion was benign. With Immunohistochemical staining invasiveness increased from benign (continuous staining) to malignant (absence of staining) end in the spectrum of prostatic lesions.Basal cell markers play significant role in the diagnosis of prostatic lesions especially which fall in the premalignant category and which create difficulty in the diagnosis by routine histopathological study.